Effects of the neonicotinoid insecticides Thiamethoxam and imidacloprid on metamorphosis of the toad rhinella arenarum at environmentally-relevant concentrations - Brodeur, Celine Marie (2023)
The present study examined the acute and chronic toxicity of the neonicotinoid insecticides imidacloprid (IMI) and thiamethoxam (TIA) on the neotropical amphibian species Rhinella arenarum, Rhinella fernandezae and Scinax granulatus. The median lethal concentration after 96 hr exposure (96 hr-LC50) ranged between 11.28 and >71.2 mg/L amongst all species and development stages tested, indicating that these pesticides are not likely to produce acute toxicity in the wild. The subchronic toxicity was also low, with 21 day-LC50 values ranging between 27.15 and >71.2 mg/L. However, tadpoles of Rhinella arenarum exposed to thiamethoxam from stage 27 until completion of metamorphosis presented a significantly lower metamorphic success rate together with a smaller size at metamorphosis, starting from the lowest concentration tested. Although a number of studies previously examined the effects of neonicotinoids on amphibian tadpoles, these investigations focused on the time to metamorphosis and reported a variety of results including retardation, acceleration or lack of effect. Here, data demonstrated that thiamethoxam predominantly impacts metamorphosis through reduction of the transformation success and body weight, rather than by affecting the timings of metamorphosis. By closely monitoring progression of tadpoles through the different stages, impairment of metamorphosis was demonstrated to occur during the transition from stage 39 to 42, suggesting an effect on the thyroid system. An asymmetry in the length of the arms was also observed in metamorphs treated with thiamethoxam. Overall, these results indicate that thiamethoxam, and conceivably other neonicotinoids, have the potential to significantly impair metamorphosis of amphibians and diminish their performance and survival in the wild.